Aproximación al estudio evolutivo de las formas organizacionales - Henríquez Barráez, Aracely Teresa (2018)
The objective ofthis article is to present through a documentary analysis a description of the main organizational forms adopted by companies, based on the theoretical comparison of the contributions made by authors such as Chiavenato (2002), Rivas (2002), Padilla and Del Aguila (2003), Velarde, et al. (2003), as well as added value propose some constitutive elements of an alternative systemic organizational form resulting from the reflection of the presented structural configurations. Among the organizational forms described are: the Mintzberg’s organic model; horizontal organization, network type organization, cellular organization and virtual organization. Product of the assessment of organizational needs in contemporary times, it is concluded that organizations must abandon the rigid, bureaucratic and normative forms to adopt a more adaptive configuration, with strategic thinking, management of authority and decentralized power, based on consensus, cooperation and whose main characteristic must be flexibility.